A development of Micro Takaful product: a case study in Malaysia / Norfaezah Mohd Shahren… [et al.] - Mohd Shahren, Norfaezah; Ismail, Maymunah; Ab Kadir, Mohd Sufian; Mohd Yusoff, Saloma (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The growth of Islamic finance has been tremendous especially in the recent years. Globally many countries have accepted the concept of Islamic finance. Besides the banking industry, insurance industry has also been affected with this so-called 'Islamic phenomena'. In Malaysia, Islamic banking and takaful have been given special attention. Even though, takaful is still a nascent industry, it has shown amazing resilience during several consecutive financial crises. There is a strong support from the government and the industry players to make it a success. Currently, there are more than 200 takaful operators globally and twelve takaful operators in Malaysia. The dependent variable for this paper is the importance of micro takaful to lower income group. Whereas the independent variables, firstly is the level of income, secondly is the promotion from the takaful operators and lastly the perception of people towards the micro takaful itself. The issue is insurance policies and takaful certificates are usually bought by those who are affordable. The lower income group unfortunately needs more protection since they cannot afford to protect themselves in the event of loss or misfortune. They need society's help to ensure their survivorship being protected, assisted and given a peace of mind.